CURRENT POSSIBILITIES AND POTENTIAL DEVELOPMENT OF MOLECULAR ENTEROVIRUS SURVEILLANCE. EXPERIENCE OF RUSSIAN FEDERATION - A. N. Lukashev (Sankt-Peterburg : NIIÈM imeni Pastera, 2018)
Abstract. Enteroviruses are small RNA viruses, which are ubiquitous and commonly cause outbreaks with various clinical manifestations. In 2006, the Program on enterovirus surveillance was approved in the Russian Federation. Over the last years, molecular-biological and bioinformatics methods for enterovirus epidemiology studies have been developed both in Russia and worldwide. Currently, identification of enteroviruses is carried out by analyzing nucleotide sequence of the full-length VP1 genome region (ca. 900 nt). Routinely, it is sufficient to obtain a partial VP1 genome region sequence (ca. 300 bp) for enteroviruse verification in most cases; however, a more stringent type criterion of 80% sequence identity should be used compared to the 75% sequence identity cut-off for the complete VP1 genome region. Further sequence analysis may be performed by using Bayesian phylogenetic methods, which allow using molecular clock to trace outbreak emergence. Enteroviruses accumulate about 0.5–1% nucleotide substitutions per year. Therefore, a short genome fragment may be used to analyze virus phylodynamics at the level of international transfers and circulating virus variants. On a shorter timescale, a full-length VP1 genome region or a complete genome sequence are preferred for investigating molecular epidemiology, because a short sequence allows to reliably distinguish not more than 1–2 transmission events per year. Thus, determining enterovirus sequences for full-length VP1 genome region or full-genome sequence is preferred for examining viral outbreaks. It is increasingly apparent that analyzing available enterovirus nucleotide sequences reveals limitations related to uneven surveillance efficacy in various countries and short length of genome fragment measured in routine control. As a result, a proper global-scale analysis of enterovirus molecular epidemiology remains problematic. Over the last 20 years, the number of available enterovirus nucleotide sequences increased by hundred times, but understanding emergence of enterovirus infection outbreaks remains limited. Further development of enterovirus surveillance would require new methods for sewage monitoring, affordable high-throughput sequencing and harmonization of global surveillance systems.